2012
DOI: 10.1016/j.ijsolstr.2012.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Laminated beams with viscoelastic interlayer

Abstract: a b s t r a c tWe analytically solve the time-dependent problem of a simply-supported laminated beam, composed of two elastic layers connected by a viscoelastic interlayer, whose response is modeled by a Prony's series of Maxwell elements. This case applies in particular to laminated glass, a composite made of glass plies bonded together by polymeric films. A practical way to calculate the response of such a package is to consider also the interlayer to be linear elastic, assuming its equivalent elastic moduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 14 publications
2
71
0
1
Order By: Relevance
“…Norville [16] and Galuppi and Royer-Carfagni [5,6] pointed out that the response of laminated glass beams presents two borderlines: 1) The layered limit corresponding to the case when the beam consists of free-sliding glass plies and 2) the monolithic limit, when the Euler-Bernoulli assumptions hold for the entire section of the laminate glass element. Hereafter we will denote the monolithic critical load as P crit 0 and the layered limit as P crit ∞ .…”
Section: Buckling Design Of Multilayered Glass Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Norville [16] and Galuppi and Royer-Carfagni [5,6] pointed out that the response of laminated glass beams presents two borderlines: 1) The layered limit corresponding to the case when the beam consists of free-sliding glass plies and 2) the monolithic limit, when the Euler-Bernoulli assumptions hold for the entire section of the laminate glass element. Hereafter we will denote the monolithic critical load as P crit 0 and the layered limit as P crit ∞ .…”
Section: Buckling Design Of Multilayered Glass Beamsmentioning
confidence: 99%
“…The concept of effective thickness has been proposed in recent years [4,5,6] based on the quasi-elastic solution. This method consists of calculating the thickness (time and temperature dependent) of a monolithic element with bending properties equivalent to those of the laminated one, that is to say, the deflections provided by the equivalent monolithic beam are equal to those of the layered model with viscoelastic core.…”
Section: Introductionmentioning
confidence: 99%
“…But their benefits go far beyond these characteristics because it is also possible to obtain mechanical properties on demand, this means that it is possible to obtain a desired strength defining a given stacking sequence of layers whose maximum strength is oriented towards strategic directions. Further, due to the resin used as matrix and transferring the stresses to the fibers, these materials also exhibit a higher damping characteristics than the observed on metals, which results on a better capacity to dissipate vibrations (Galuppi and Royer-Carfagni 2012). These, and many other characteristics besides the mechanical ones, make laminated composites attractive to very critical structures where simulations are very important to predict their mechanical behaviors; however, the mismatch of properties between fibers and resin-producing localized strains makes important to be able to develop simulations not only at the highest scales to account for global deformations, but also in lower scales to develop advanced and optimized material properties or to understand the feasibility to develop a failure.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental characteristic of viscoelastic materials is that the mechanical properties are frequency (or time) and temperature dependent [12,13,14,15]. The mechanical behavior of laminated glass is not elastic and the sections do not behave according to the Euler-Bernoulli Beam theory assumptions (plane sections remain plane) due to the shear effect of the interlayers [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Galuppi and Royer-Carfagni [1] concluded that a full viscoelastic analysis is only recommended when one is interested in a precise design of a laminated glass structures. Bennisson et al [3,4] proposed the concept of effective thickness for simplifying calculations of laminated glass elements under static loading, based on a previous work developed by Wölfel [17].…”
Section: Introductionmentioning
confidence: 99%